Comparison of Two Maintenance Training Arrangements with Instructive Feedback in Children with Autism - Matos, Daniel Carvalho; Loureiro, Danielle Juliana Ribeiro; Silva, Katiane Reis; Galvão, Pollianna (Advances in Social Sciences Research Journal, 2024)
Instructive feedback (IF) can improve the efficiency of teaching in children with autism spectrum disorder (ASD) by establishing emergent skills. The purpose of this study was to compare the effects of two types of listener responding maintenance teaching with IF on acquisition of four untaught repertoires in three children with ASD. In one of the teaching cases, attending and tact responses of visual stimuli were required. The emergence was partial for all learners, with no great difference in the efficiency of the types of teaching. Two of the new repertoires were not demonstrated. Errorless performance of some relations was shown by all, but for only one child immediate emergence was verified. The results were discussed regarding the possibility of new investigations on alternative procedure to IF that could produce the emergence of new repertoires.